Analisis Tingkat Pengungkapan Laporan Keuangan Pemerintah Daerah di Sumatera - Mohammad Luthfi; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to determine the level of financial reporting disclosure of provincial/district/city governments in Sumatra in 2020. The study population was 164 local government financial reports. The sampling technique used is a saturated sampling technique, namely a sampling technique that uses all members of the population as a sample. The data used is secondary data in the form of data and information on financial statements of provincial/district and city governments in Sumatra. This study uses 7 disclosure indicators, with a total of 302 mandatory disclosures. The results show that the level of disclosure in the financial statements of provincial/district and city governments in Sumatra is still low. The average level of disclosure is 54.47%. In future research, it is expected to conduct interviews and observations to identify the factors that cause high and low disclosures in local government financial statements.